Genética populacional de mosquitos vetores: ferramenta para controle de malária, dengue e zika - salgueiro, P. (Livro de Resumos do XVII Congresso Ibérico de Entomologia, 2016)
In order to better understand and predict disease epidemiology, clear knowledge about the basic biology of the organisms involved is crucial. Advances in both molecular genotyping methodologies and theoretical developments have contributed to the increasing impact of such approaches on the understanding of vector-borne infectious diseases. Gene flow pattern and population structure of vector populations can influence the design of control strategies to decide the appropriate thresholds needed to halt the transmission of the disease. In this context, I will present an overview of some recent population genetic studies on Anopheles sp. and Aedes aegypti and the implications for the transmission of malaria, dengue and zika.